Finite Element Simulation of FRP-Strengthened Thin RC Slabs - Assad, Maha (2022)
This study aims to investigate the flexural behavior of high-strength thin slabs externally strengthened with fiber-reinforced polymer (FRP) laminates through a numerical simulation. A three-dimensional (3D) finite element (FE) model is created to simulate the response of strengthened reinforced concrete (RC) slabs under a four-point bending test. The numerical model results in terms of load-deflection behavior, and ultimate loads are verified using previously published experimental data in the literature. The numerical results show a good agreement with the experimental results. The FE model is then employed in a parametric study to inspect the effect of concrete compressive strength on the performance of RC thin slabs strengthened with different FRP types, namely carbon fiber-reinforced polymers (CFRP), polyethylene terephthalate fiber-reinforced polymers (PET-FRP), basalt fiber-reinforced polymers (BFRP) and glass fiber-reinforced polymers (GFRP). The results showed that the highest strength enhancement was obtained by the slab that was strengthened by CFRP sheets. Slabs that were strengthened with other types of FRP sheets showed an almost similar flexural capacity. The effect of concrete compressive strength on the flexural behavior of the strengthened slabs was moderate, with the highest effect being a 15% increase in the ultimate load between two consecutive values of compressive strength, occurring in the CFRP-strengthened slabs. It can thus be concluded that the developed FE model could be used as a platform to predict the behavior of reinforced concrete slabs when strengthened with different types of FRP composites. It can also be concluded that the modulus of elasticity of the composite plays a major role in determining the flexural capacity of the strengthened slabs.